Vancomycin-Loaded Polycaprolactone Electrospinning Nanofibers Modulate the Airway Interfaces to Restrain Tracheal Stenosis - Zhao, Yanan; Tian, Chuan; Wu, Kunpeng; Zhou, Xueliang; Feng, Kexing; Li, Zhaonan; Wang, Zijian; Han, Xinwei (Frontiers in Bioengineering and Biotechnology, 2021)
Achieving site-specific release of therapeutics at trachea infection sites remains a great challenge in clinic. This work aims to develop a series of polycaprolactone (PCL) and vancomycin (VA) nanofiber films (PVNF-n, n = 0, 1, and 5, respectively) via electrospinning. The efficacy of PVNF-n was evaluated for its physiochemical analysis and antibacterial property. The results of FITR, XRD, SEM-EDS and drug release indicated that VA were successfully introduced into PCL, and can be sustained released from films, as well as the PVNF-n displayed a network structure of fibers with random directions. Importantly, the PVNF-5 showed superb antibacterial efficacy against Methicillin-resistant Staphylococcus aureus (MRSA) and Streptococcus pneumoniae (SPn). Furthermore, the PVNF-5 films were covered onto the self-expandable metallic stent to construct anti-infection airway stent, and then implant into the New Zealand Rabbits model to repair tracheal stenosis. Compared to the bare metal airway stent, commercial pellosil-matrix covered airway stent and PVNF-0 covered airway stent, PVNF-5 covered airway stent showed reduced granulation tissue thickness, collagen density, α-SMA, CD68, TNF-α, IL-1 and IL-6 expression. In conclusion, this work provides an anti-infection films-covered airway stent that in-site restrain trachea stenosis.